2015
DOI: 10.12659/msm.893128
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Cold-Inducible RNA-Binding Protein (CIRP) in Pituitary Adenoma and its Relationships with Tumor Recurrence

Abstract: BackgroundThe aim of this study was to detect the expression of cold-inducible RNA-binding protein in pituitary adenoma and to determine its effects on tumor recurrence.Material/MethodsWe collected a total of 60 post-op samples collected from pituitary adenoma patients (including 20 cases of invasive pituitary adenoma, 20 cases of non-invasive adenoma, and 20 cases of non-invasive recurrent adenoma) admitted in our hospital. Both protein and mRNA levels of CIRP in 3 types of pituitary adenoma samples were quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Clinically, we showed that patients with higher CIRP expression are more likely to recur than those with rare or no CIRP expression; Moreover, in postoperative recurrent patients, CIRP expression levels in sample from secondary surgery were remarkably higher than that from the initial one, which indicated that CIRP is correlated with recurrence. This result is consistent with the finding reported in a recent study that recurrent pituitary adenoma expressed significantly higher CIRP levels compared to non-recurrent tumors and CIRP expression is correlated with tumor proliferation and invasion [ 21 ]. CIRP, thus, might be a marker for predicting the risk of CD recurrence.…”
Section: Discussionsupporting
confidence: 93%
“…Clinically, we showed that patients with higher CIRP expression are more likely to recur than those with rare or no CIRP expression; Moreover, in postoperative recurrent patients, CIRP expression levels in sample from secondary surgery were remarkably higher than that from the initial one, which indicated that CIRP is correlated with recurrence. This result is consistent with the finding reported in a recent study that recurrent pituitary adenoma expressed significantly higher CIRP levels compared to non-recurrent tumors and CIRP expression is correlated with tumor proliferation and invasion [ 21 ]. CIRP, thus, might be a marker for predicting the risk of CD recurrence.…”
Section: Discussionsupporting
confidence: 93%
“…High level of CIRP in human oral squamous cell carcinoma is associated with a short survival rate [ 73 ]. CIRP expression level is also positively associated the invasive ability of pituitary adenoma in human [ 74 ]. An integrated analysis of serum autoantibody expression profiling in patients with breast cancer, found that serum autoantibody targeting CIRP was significantly increased in patients with breast carcinoma and its change can be used as a prognostic biomarker for cancer progression [ 75 ].…”
Section: The Rna-dependent Function Of Cirp: a Cell Autonomous Functimentioning
confidence: 99%
“…In pituitary adenoma, high CIRP expression correlates with proliferating invasive and recurrent tumor, probably via ERK1/2 signaling pathway [ 102 , 139 ]. In oral squamous cell carcinoma, CIRP is co-expressed with TLR4 and is associated with a short survival rate [ 140 ].…”
Section: Regulation and Functions Of Cirpmentioning
confidence: 99%